USING NONCONTINGENT REINFORCEMENT TO INCREASE COMPLIANCE WITH WEARING PRESCRIPTION PROSTHESES - Richling, Sarah M (The Society for the Experimental Analysis of Behavior, 2011)
We evaluated the effects of noncontingent reinforcement (NCR) on compliance with wearing foot orthotics and a hearing aid with 2 individuals. Results showed that NCR increased the participants' compliance with wearing prescription prostheses to 100% after just a few 5-min sessions, and the behavior change was maintained during lengthier sessions. The results are discussed in terms of the potential value-altering effects of NCR.